Epstein–Barr virus–driven molecular pathogenesis of primary pulmonary lymphoepithelial carcinoma - Xie, Mingyuan; Yao, Dong; Lei, Liping; Tang, Chengjiang; Mo, Biwen (Frontiers in Oncology, 2025)
Primary Pulmonary Lymphoepithelial Carcinoma (PLEC) is a rare subtype of non-small cell lung cancer (NSCLC) that exhibits a strong association with Epstein–Barr virus (EBV) infection and shows distinctive geographic and ethnic predilections. Over the past decades, significant efforts have been made to elucidate the pathogenic mechanisms of PLEC, and progress in diagnosis, treatment, and disease monitoring has been achieved. This review focuses on EBV-driven oncogenic mechanisms in PLEC and explores the relationship between EBV infection, tumor progression, and clinical prognosis. We further summarize the molecular pathology, tumor immune microenvironment, and clinicopathological characteristics of PLEC. These insights may offer a theoretical foundation for EBV-targeted and immunotherapeutic strategies in PLEC.